La langue régionale : une marque de terroir ? - Fatiha Fort (Lengas)
The terroir associated with food products is often considered by marketing as a sign of quality because of the strong links it suggests with the geographical origin, traditions and know-how of the producers. We show in this paper that language can be used to embed the product in the territory of the language and give it a quality linked to the local and proximity dimensions. Beyond the search for quality, the interviewees highlight the emotional links with the language but also the militant and political motivations to defend a language and a regional culture. We also note that no specificity or typicality of products claiming to be Occitan is required and that only the place of production in Occitanie counts as a proof of legitimacy. In practice, the use of Occitan divides the respondents on the type of writing to be used to display the names of products.